Modulation of alpha smooth muscle actin and desmin expression in perisinusoidal cells of normal and diseased human livers. - Schmitt-Gräff, A. (1991)
It has been suggested that perisinusoidal liver cells (PSC) play a pivotal role in the pathogenesis of fibrocontractive changes. Using light and electron microscopic immunolocalization techniques, a series of 207 normal and pathologic human liver specimens were evaluated for the expression of alpha smooth muscle (SM) actin and desmin in this and other nonparenchymal cell types. In normal adult liver tissue, PSCs were practically devoid of desmin and exceptionally stained for alpha-SM actin, whereas this actin isoform frequently was encountered in PSCs from the embryonic to the adolescent period. A broad spectrum of pathologic conditions was accompanied by the presence of alpha-SM actin containing PSCs; these were detected preferentially in periportal or perivenular zones according to the predominant location of the underlying hepatocellular damage. The occurrence of this PSC phenotype generally was associated with fibrogenesis and was in some cases detected earlier than overt collagen accumulation. Fibrous bands subdividing liver tissue in cirrhosis and focal nodular hyperplasia, as well as desmoplastic reaction to malignant tumors, contained alpha-SM actin-rich cells admixed with variable proportions of cells coexpressing desmin. In end stages, this population was less numerous than in active fibrotic or cirrhotic processes. Using immunogold electron microscopy, alpha-SM actin was localized in microfilament bundles of typical PSCs. Our results are compatible with the assumption that the appearance of alpha-SM actin and desmin-expressing myofibroblasts results at least in part from a phenotypic modulation of PSCs.